Prognostic implications of fractional flow reserve and coronary flow reserve after newer-generation drug-eluting stent implantation. (3rd October 2022) - Ueno, H; Hoshino, M; Sugiyama, T; Kanaji, Y; Hada, M; Misawa, T; Nagamine, T; Nogami, K; Sayama, K; Matsuda, K; Yonetsu, T; Sasano, T; et al.
Abstract: Background: FFR after percutaneous coronary intervention (PCI) has been reported to provide prognostic information. However, limited data are available regarding the prognostication by CFR in patients treated with elective PCI using newer generation DES. Purpose: This study aimed to assess the prognostic value of post-procedural fractional flow reserve (FFR) and coronary flow reserve (CFR) after newer-generation drug-eluting stent implantation (DES). Methods: A total of 466 stenoses in 466 patients underwent FFR-guided PCI. FFR and CFR measurements before and after PCI by a pressure-temperature sensor-tipped wire were performed. Follow-up data were studied to determine the predictors of target vessel failure (TVF), defined as death, target vessel-related nonfatal myocardial infarction, and unplanned clinically driven target vessel late revascularization. Prognostic value of post-PCI CFR was compared with that of FFR or FFR/CFR combination. Results: After PCI completion, 13.7% showed post-PCI FFR ≤0.80 and 44.2% exhibited post-PCI CFR <2.5. Discordant results were observed in 42.5% (198/466). During 2.7 (1.8–3.3) years follow-up, 57 (12.2%) TVF were documented. The multivariable Cox proportional hazard regression analysis revealed that post-PCI FFR and post-PCI CFR were independent prognostic factors. ROC analysis revealed that the optimal cut-off values of post-PCI FFR and CFR values were 0.85 and 2.26, respectively. Significant differences in TVF were detected according to post-PCI FFR (≤0.85 vs >0.85: 17.8% vs 8.9%, P<0.05) and post-PCI CFR (≤2.26 vs >2.26: 20.5% vs 7.2%, P<0.01), although the reclassification ability for TVF was improved only with post-PCI CFR (net reclassification index 0.598; P<0.01; integrated discrimination index 0.038; P<0.01), but not with post-PCI FFR, in comparison with the clinical model. Compared with patients with FFR >0.85, those with post-PCI FFR ≤0.85 and CFR ≤2.26 showed significantly higher risk of TVF (8.9% vs 28.9%, P<0.01, HR 4.24, 95% CI 2.40–7.50, P<0.01), whereas those with post-PCI FFR <0.85 and CFR >2.26 had similar TVF risk (8.9% vs 9.2%, P=1.00, HR 1.01, 95% CI 0.47–2.16, P=0.97). Conclusions: After PCI completion with newer-generation DES, discordant results between FFR and CFR were observed in 42.5%. Compared with post-PCI CFR, post-PCI FFR provided limited reclassification ability for TVF. Among patients with lower post-PCI FFR, only patients with lower post-PCI CFR showed significantly higher risk of TVF than those with higher post-PCI FFR. Funding Acknowledgement: Type of funding sources: None.